Treatment sequencing in metastatic colorectal cancer - Torounidou, Nanteznta; Yerolatsite, Melina; Zarkavelis, George; Amylidi, Anna-Lea; Karafousia, Vaia; Kampletsas, Eleftherios; Mauri, Davide (Contemporary Oncology/Współczesna Onkologia, 2024)
Metastatic colorectal cancer (mCRC) remains a significant challenge in contemporary oncology, with treatment sequencing playing a pivotal role in reported patient outcomes. Although currently available therapeutic options have led to improved median overall survival rates, the prognosis for patients with stage IV disease still remains dismal. This article provides a comprehensive review of the current landscape of treatment sequencing strategies in mCRC, focusing on the rationale behind various approaches and the evolving evidence supporting their efficacy. We consider the roles of chemotherapy, targeted therapy, and immunotherapy agents, as well as emerging trends in personalized medicine and sequential therapy regimens. The concept of a “continuum of care” has emerged as a fundamental principle, aiming to provide all available therapies through an individualized approach to maximize clinical benefit. By elucidating the underlying complexities of treatment sequencing in mCRC, this review aims to guide clinicians in optimizing therapeutic strategies and improving patient care.